Double-strand breaks induce short-scale DNA replication and damage amplification in the fully grown mouse oocytes. Issue 2 (1st April 2021) - Ma, Jun-Yu; Feng, Xie; Xie, Feng-Yun; Li, Sen; Chen, Lei-Ning; Luo, Shi-Ming; Yin, Shen; Ou, Xiang-Hong
Abstract: Break-induced replication (BIR) is essential for the repair of DNA double-strand breaks (DSBs) with single ends. DSBs-induced microhomology-mediated BIR (mmBIR) and template-switching can increase the risk of complex genome rearrangement. In addition, DSBs can also induce the multi-invasion-mediated DSB amplification. The mmBIR-induced genomic rearrangement has been identified in cancer cells and patients with rare diseases. However, when and how mmBIR is initiated have not been fully and deeply studied. Furthermore, it is not well understood about the conditions for initiation of multi-invasion-mediated DSB amplification. In the G2 phase oocyte of mouse, we identified a type of short-scale BIR (ssBIR) using the DNA replication indicator 5-ethynyl-2'-deoxyuridine (EdU). These ssBIRs could only be induced in the fully grown oocytes but not the growing oocytes. If the DSB oocytes were treated with Rad51 or Chek1/2 inhibitors, both EdU signals and DSB marker γH2A.X foci would decrease. In addition, the DNA polymerase inhibitor Aphidicolin could inhibit the ssBIR and another inhibitor ddATP could reduce the number of γH2A.X foci in the DSB oocytes. In conclusion, our results showed that DNA DSBs in the fully grown oocytes can initiate ssBIR and be amplified by Rad51 or DNA replication.